Canadian Society of Nephrology Commentary on the Kidney Disease Improving Global Outcomes 2017 Clinical Practice Guideline Update for the Diagnosis, Evaluation, Prevention, and Treatment of Chronic Kidney Disease-Mineral and Bone Disorder. (August 2020) - Holden, Rachel M.; Mustafa, Reem A.; Alexander, R. Todd; Battistella, Marisa; Bevilacqua, Micheli U.; Knoll, Greg; Mac-Way, Fabrice; Reslerova, Martina; Wald, Ron; Acott, Philip D.; Feltmate, Patrick; Grill, Allan; et al.
Purpose of review: (1) To provide commentary on the 2017 update to the Kidney Disease Improving Global Outcomes (KDIGO) 2017 Clinical Practice Guideline Update for the Diagnosis, Evaluation, Prevention, and Treatment of Chronic Kidney Disease-Mineral and Bone Disorder (CKD-MBD); (2) to apply the evidence-based guideline update for implementation within the Canadian health care system; (3) to provide comment on the care of children with chronic kidney disease (CKD); and (4) to identify research priorities for Canadian patients. Sources of information: The KDIGO 2017 Clinical Practice Guideline Update for the Diagnosis, Evaluation, Prevention, and Treatment of CKD-MBD. Methods: The commentary committee co-chairs selected potential members based on their knowledge of the Canadian kidney community, aiming for wide representation from relevant disciplines, academic and community centers, and different geographical regions. Key findings: We agreed with many of the recommendations in the clinical practice guideline on the diagnosis, evaluation, prevention, and treatment of CKD-MBD. However, based on the uncommon occurrence of abnormalities in calcium and phosphate and the low likelihood of severe abnormalities in parathyroid hormone (PTH), we recommend against screening and monitoring levels of calcium, phosphate, PTH, and alkaline phosphatase in adults with CKD G3. We suggest and recommend monitoring these parameters in adults with CKD G4 and G5, respectively. In children, we agree that monitoring for CKD-MBD should begin in CKD G2, but we suggest measuring ionized calcium, rather than total calcium or calcium adjusted for albumin. With regard to vitamin D, we suggest against routine screening for vitamin D deficiency in adults with CKD G3-G5 and G1T-G5T and suggest following population health recommendations for adequate vitamin D intake. We recommend that the measurement and management of bone mineral density (BMD) be according to general population guidelines in CKD G3 and G3T, but we suggest against routine BMD testing in CKD G4-G5, CKD G4T-5T, and in children with CKD. Based on insufficient data, we also recommend against routine bone biopsy in clinical practice for adults with CKD or CKD-T, or in children with CKD, although we consider it an important research tool. Limitations: The committee relied on the evidence summaries produced by KDIGO. The CSN committee did not replicate or update the systematic reviews.